BOLHÔMETRO DIGITAL: CONSTRUÇÃO DE INSTRUMENTO DE MEDIDA DE VAZÃO GASOSA BASEADO EM TRANSMITÂNCIA DE LUZ EM FAIXAS DE 15-150 mL min-1 - Igor R. Neves; André J. R. Simões; Leandro R. Teixeira; Juliane G. C. Gomes; Soraia T. Brandão; Iuri M. Pepe (Química Nova)
Gas flow measurement is a necessity in many areas of chemical research. One equipment used for this end is the bubblemeter or soap-flowmeter. The principle of this instrument is based on measuring the time it takes for a thin film of soap - a bubble - to move through an area with a known volume. The analog version of this equipment present limitations, such as the dependence on analyst monitoring and the associated ergonomic risk. This work presents the development of a digital soap flowmeter portable and autonomous. The instrument uses light emitting diode (LED)-photodiode pairs, a signal treatment system and microcontroller for operating independently of a PC or laptop. This work automated the detection of the thin film passage for measuring the initial and final times of detection, thereby minimizing errors present in analog bubblemeters. For ensuring precision, the instrument was calibrated with an analog bubblemeter. Additionally, tests with multiple gases were conducted for validating the results, whereupon digital and analog soap-flowmeters were satisfactorily concordant. The portability and precision of the designed device ensure it is adequate for laboratorial and field usage, guaranteeing quick and safety in the measurement of gaseous flow.